Spontaneous cryptococcal peritonitis with fungemia in patients with decompensated cirrhosis: Report of two cases - Bal, Chinmaya Kumar (Medknow Publications & Media Pvt Ltd, 2014)
Cryptococcus neoformans is encapsulated yeast that predominately infects immunocompromised individuals. Liver disease is an under-recognized predisposition for cryptococcal disease. We report two nonalcoholic, nondiabetic, and human immunodeficiency virus - negative cirrhotic patients, with spontaneous cryptococcal peritonitis. Cryptococcus infection was diagnosed by culture of ascitic fluid and peripheral blood in both. We treated the first patient with amphotericin-B, but he expired. The second patient with earlier diagnosis, survived to discharge with fluconazole treatment. We suggest a high clinical suspicion for Cryptococcus as a possible etiology of spontaneous peritonitis in cirrhotic patients.